Unified line-of-sight: A guidance algorithm with integral wind-up mitigation and turning assist for USVs - Tanakitkorn, Kantapon; Phoemsapthawee, Surasak; Thaweewat, Nonthipat; Jungrungruengtaworn, Sirirat (Ocean engineering, 2024)
Guidance algorithm is a key part in waypoint navigation for USVs. In this paper, a novel guidance algorithm named the unified line-of-sight (ULOS) is introduced. The ULOS algorithm is developed based on the concept of the integral-based LOS algorithm. However, a special technique is employed in the ULOS algorithm to address the integral wind-up issue commonly found in other integral-based LOS algorithms in the literature. In addition, a heading compensation term based on sway velocity is incorporated into the algorithm. This sway compensation term enhances the vehicle’s ability to execute sharp turns effectively. The ULOS algorithm was benchmarked against four existing guidance algorithms in various tasks through numerical simulations. The comprehensive results have revealed the superior performance of the ULOS algorithm over the other algorithms. •A novel guidance algorithm named the unified line-of-sight (ULOS) is introduced.•The ULOS uses a unique technique to address integral wind-up.•A sway compensation is added to enhance the vehicle’s ability in sharp turns.•The ULOS has been benchmarked against four existing guidance algorithms.•The ULOS is able to handle the external disturbance with superior performance.